Esophageal epithelial immunoglobulin G is an important marker for the diagnosis and management of pediatric eosinophilic esophagitis. Issue 6 (14th May 2022) - Rizvi, Syed Ahsan; Oriala, Chukwuemeka; Irastorza, Laura E; Bornstein, Jeffrey; Li, Shuan; Smadi, Yamen
Abstract: Background and Aim: Our primary aim was to describe the prevalence of immunoglobulin G (IgG) and its subclass IgG4 in immunohistochemistry staining in esophageal biopsy specimens of children with eosinophilic esophagitis (EoE) compared with that of specimens from children with gastroesophageal reflux disease (GERD). Methods: Esophageal biopsy specimens from children with EoE or GERD were stained prospectively for IgG and IgG4 antibodies. Subjects with EoE were divided into cohorts with either active EoE or EoE in remission. Active EoE cases were further divided into proton pump inhibitor responsive (PPI‐r) and PPI‐nonresponsive (PPI‐nr) subgroups. Demographic, clinical, and histologic data were compared among groups, including quantified IgG and IgG4 staining, peak eosinophil count, eosinophil‐derived neurotoxin levels, and EoE endoscopic reference score. Results: Seventy‐nine children (aged 10.6 ± 5.6 years; 68% male) were enrolled. IgG‐positive cell counts were significantly elevated in those with active EoE ( n  = 29, 3 [interquartile range, IQR: 2–6]/high‐powered field [HPF]), compared with those having EoE remission ( n  = 25, 1 [IQR: 0–2]/HPF; P  = 0.002) and those with GERD ( n  = 25, 0 [IQR: 0–0.25]/HPF, P  = <0.0001). IgG‐positive cell counts were significantly higher in the PPI‐r ( n  = 15, 5 [IQR: 2.5–11]/HPF) subgroup, compared with the PPI‐nr subgroup ( n  = 11, 3 [IQR: 1.5–3.5]/HPF; P  = 0.041) at baseline endoscopy. Conclusion: Initial esophageal tissue biopsy specimens from pediatric subjects with active EoE showed a significant increase in IgG‐positive staining compared with tissue from subjects in EoE remission or with GERD. There was higher positivity of IgG‐stained cells in the PPI‐r subgroup compared with the PPI‐nr subgroup. Abstract : Initial esophageal tissue biopsies from pediatric subjects with active eosinophilic esophagitis (EoE), showed a significant increase in immunoglobulin G (IgG)‐positive staining, compared with tissue from subjects in EoE remission or with gastrointestinal reflux disease. There was higher positivity of IgG‐stained cells in the proton pump inhibitor (PPI) responsive subgroup, compared with the PPI‐nonresponsive subgroup. Further study of IgG and IgG4 immunostaining of esophageal biopsies of pediatric patients with EoE is needed to clarify the use of specific immunoglobulin subclasses as disease‐specific and potentially treatment‐specific biomarkers.